Effects of Microbial Fermented Feed on Serum Biochemical Profile, Carcass Traits, Meat Amino Acid and Fatty Acid Profile, and Gut Microbiome Composition of Finishing Pigs - Tang, Xiaopeng; Liu, Xuguang; Zhang, Kai (Frontiers in Veterinary Science, 2021)
Microbial fermented feed is an important part of feed industry, while little research has focused on the solid-state fermentation of complete feed. Herein, the purpose of the present study was to investigate the effects of fermented complete feed (FCF) on the growth performance, biochemical profile, carcass traits, meat proximate composition, meat amino acid and fatty acids profile, and gut microbiome composition of finishing pigs, thereby providing references for the application of FCF in animal production. Twenty Duroc× Landrace× Yorkshire pigs with an average body weight (BW) of (48.74 ± 1.49) kg were divided randomly into control group (pigs received a basal diet, CN, n=10) and FCF group (pigs fed with FCF, n=10). The experiment lasted for 60 days. FCF improved the growth performance, which indicated by a significantly increased of finally body weight, average daily gain (ADG) and average daily feed intake (ADFI), and a significantly decreased of feed to gain ratio (F/G). FCF improved biochemical profile, which indicated by a higher ALP, GLU, IgG, IgM, SOD and T-AOC content. Pigs received FCF had a better carcass traits and meat quality than pigs received basal diet, which indicated by a higher carcass length, crude protein content, lysine content, Glu content, C18:ln9c, C18:2n6c, C20:4n6 and unsaturated fatty acids content, and a lower average backfat thickness, C18:0 and saturated fatty acids. FCF significantly reduced the relative abundances of presumably pathogenic bacteria of phylum Proteobacteria and genus Escherichia-Shigella, and enhanced the relative abundances of likely beneficial bacteria of phylum Firmicutes and genus Clostridium. In summary, FCF had a certain effect on the improvement of growth performance, serum biochemical profile, carcass traits, meat proximate composition, amino acid and fatty acids profile, and gut microbiome composition of finishing pigs